Assesment of heavy metals in Razor clams (Solen spp) collected from Asajaya Laut, Kota Samarahan - Roland, Laiping. (Universiti Malaysia Sarawak (UNIMAS), 2006)
This study was carried out to determine the concentration of heavy metals in razor clams at Asajaya Laut. Sediment samples and water samples were also coJlected during the sampling. Sediment samples and razor clams were collected from 9 stations at three different tidal zones. Analysis of Co, Cu, Mn, Pb and Zn were carried out flame atomic absorption spectrophotometry (FAAS). Water quality results showed no variation between the two samplings. Mn recorded the highest concentration in sediment and razor clam samples. While Co and Pb displayed the lower concentrations. Correlation study between concentrations of heavy metals in tissue with the shell sizes showed good relationship for Cu and Zn with the increasing shell length. There was no significant correlation between concentration of heavy metal in sediment and razor clams except for Mn.